Near-infrared pH-switchable BODIPY photosensitizers for dual biotin/cRGD targeted photodynamic therapy - Porubský, Martin; Hodoň, Jiří; Stanková, Jarmila; Džubák, Petr; Hajdúch, Marián; Urban, Milan; Hlaváč, Jan (Journal of photochemistry and photobiology. B, Biology, 2024)
Photodynamic therapy (PDT) is a clinically-approved cancer treatment that is based on production of cytotoxic reactive oxygen species to induce cell death. However, its efficiency depends on distribution of photosensitizer (PS) and depth of light penetration through the tissues. Tendency of pathological cancer tissues to exhibit lower pH than healthy tissues inspired us to explore dual-targeted pH-activatable photosensitizers based on tunable near-infrared (NIR) boron-dipyrromethene (BODIPY) dyes. Our BODIPY PSs were designed to carry three main attributes: (i) biotin or cRGD peptide as an effective cancer cell targeting unit, (ii) amino moiety that is protonated in acidic (pH <6.5) conditions for pH-activation of the PS based on photoinduced electron transfer (PET) and (iii) hydrophilic groups enhancing the water solubility of very hydrophobic BODIPY dyes. Illumination of such compounds with suitable light (>640nm) allowed for high phototoxicity against HeLa (αvβ3 integrin and biotin receptor positive) and A549 (biotin receptor positive) cells compared to healthy MRC-5 (biotin negative) cells. Moreover, no dark toxicity was observed on selected cell lines (>10 μM) providing promising photosensitizers for tumour-targeted photodynamic therapy.
Keywords: HeLa Cells; Hydrogen-Ion Concentration; infračervené záření; lidé; HeLa buňky; Photochemotherapy; Photosensitizing Agents; A549 Cells; Infrared Rays; Boron Compounds; Biotin; fotosenzibilizující látky; biotin; cyklické peptidy; Peptides, Cyclic; Cell Survival; viabilita buněk; fotochemoterapie; sloučeniny boru; koncentrace vodíkových iontů; buňky A549; Humans